Student's guide to the Internet - Clark, David (Indianapolis, Indiana : Que Corporation, 1996)
This updated resource contains information a student might need to find the best resources on the Web, whether they are researching information for a paper, looking for a job, or just surfing the Web.
Includes index.
Keywords: INTERNET